The Social Services : The immediate problem and the way forward (London : The Socialist Medical Assocation)
1944 1944 1940s 34 pages treatment which can be laid down for the first of these. While the mentally disordered and defective remain primarily a problem for medical research, they present immediate and acute social problems, which have to be dealt with for the most part individually. An extension of treatment facilities especially on the social side is urgently needed. This involves an extension of training facilities for staff, and public funds should be made freely available for this. A contribution to the solution of some of those problems could be made by way of a drive to educate the public in mental health. The solution of the problem of delinquency is no easier. The causes of delinquency are varied, but in the long run are largely dependent on the social structure, and change as it changes. The possibility of re-habilitation of the delinquent person is also closely dependent on the economic and social structure. At present it is impossible to give prisoners constructive and useful work because of the competition for markets and for jobs, which is inherent in the capitalist system, though it is generally agreed that this is one of the most important factors in restoring confidence and self-respect. The most serious obstacle to rehabilitation is the fact that even if a person under detention has learnt to work and to enjoy working, his chance of getting a job on release is less than that of other men. In our present economic situation only piecemeal reforms can be carried 19 15X/2/464/1